CHEWING GUM CONTAINING PROPOLIS WAX FROM APIS MELLIFERA BEES FOR PREVENTION OF DENTAL CARIES DISEASE - SOEKANTO, SRI ANGKY; LEVINA, ASTRID; SHARFINA IRIANTO, EKA NURIN; ADZIMA, ACHMAD HUDA FAUZI; HERMANSYAH, HERI; WIJANARKO, ANONDHO; SAHLAN, MUHAMAD (International Journal of Applied Pharmaceutics, 2019)
Objective: Dental caries is caused by demineralization of the tooth surface by organic acids as a result of metabolism of cariogenic bacteria, especially Streptococcus mutans. Chewing gum has been proven to help prevent dental caries formation by stimulating salivary flow and thus reducing the availability of nutrients for cariogenic bacteria. Methods: In this study, sugar-free chewing gum was formulated using latex from the jelutong tree (Dyera costuata) with the addition of propolis wax (1–5%) as an antibacterial agent to inhibit the activity of S. mutans and prevent biofilm formation, which is an early disease stage of dental caries. Characterization of jelutong latex using differential scanning calorimetry and thermogravimetric analysis shows that the latex has glass transition temperatures of −22.46°C and 33.86°C, and it contains volatile (14.96%), polymer (84.43%), organic (0.36%), and inorganic (0.25%) components. The propolis wax used in this formulation mostly contains resin and wax and is a purification by-product of raw propolis obtained from Apis mellifera. Results: Flavonoids acting as antibacterial compounds are found in propolis, and presumably are also found in propolis wax; thus, probably this compound also has the antibacterial properties of propolis. The in vitro testing showed that 5% propolis wax in sugar-free chewing gum can prevent the formation of dental caries by inhibiting biofilm formation with up to 80% more effectiveness relative to negative controls (without chewing gum). Conclusion: Propolis wax chewing gum can inhibit the formation of dental caries disease.